Phosphate Glass Detectors for Heavy Ion Identification - Nassurlla Burtebayev; Mikhail Chernyavskiy; Alexei Gippius; Galina Kalinina; Nina Konovalova; Marzhan Nassurlla; Tatyana Kvochkina; Maulen Nassurlla; Natalia Okateva; Andrey Pan; Natalia Polukhina; Zhakypbek Sadykov; et al. (Universe, 2022)
The problem of the boundaries of the Mendeleev table of chemical elements is closely related to the understanding of the properties of nuclear matter. In this regard, the synthesis of superheavy nuclei on accelerators and the registration of their decay products are of fundamental scientific interest. The Joint Institute of Nuclear Research in Dubna (JINR) conducts research on the synthesis of superheavy nuclei on the new DC-280 cyclotron (the Factory of Superheavy Elements). As part of the development of this experiment, the possibility of using phosphate glass as a material for detectors of heavy and superheavy nuclei is being considered. This issue requires test experiments to study the recording properties of the glass at different irradiation and treatment conditions. The article presents a method for identifying heavy ions in phosphate glass detectors under various conditions by the geometric characteristics of ion tracks. The results obtained indicate the possibility of using the KNFS-3 phosphate glass detectors for registration and identification of accelerated superheavy nuclei.